Religious Coping in Bereaved Grandparents after a Grandchild Death - Hüseyin Çaksen, (Pakistan Journal of Medical & Health Sciences, 2023)
The death of a child is a traumatic family life event. Although parental bereavement has received substantial attention, little research has focused on the grief experiences of bereaved grandparents1. Pediatric palliative care focuses mainly on the children suffering from a life-limiting disease, but always includes parents and siblings. However, grandparents are also often highly involved in caring for the child and require additional attention2. Herein, we present religious coping in bereaved grandparents who lost their grandchildren to attract the attention of health professionals to bereaved grandparents.